1987
DOI: 10.1007/bf01869160
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of epithelial Na+ channels by a pH-dependent interaction with calcium, and by other divalent ions

Abstract: Direct inhibitory effects of Ca2+ and other ions on the epithelial Na+ channels were investigated by measuring the amiloride-blockable 22Na+ fluxes in toad bladder vesicles containing defined amounts of mono- and divalent ions. In agreement with a previous report (H.S. Chase, Jr., and Q. Al-Awqati, J. Gen. Physiol. 81:643-666, 1983) we found that the presence of micromolar concentrations of Ca2+ in the internal (cytoplasmic) compartment of the vesicles substantially lowered the channel-mediated fluxes. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…This conclusion is supported by previous data indicating that the aldosteroneinduced channels are accessible to impermeable reagents interacting with the apical surface prior to the application of the hormone (9)(10)(11). A possible mechanism for such a labile activation of transport could be release of channels from direct inhibition by cell Ca2" (22). Incubating the tissue with aldosterone for longer periods (e.g., 6-16 hr) produced an additional increase in ISC that was sustained by vesicles.…”
Section: Figuresupporting
confidence: 81%
“…This conclusion is supported by previous data indicating that the aldosteroneinduced channels are accessible to impermeable reagents interacting with the apical surface prior to the application of the hormone (9)(10)(11). A possible mechanism for such a labile activation of transport could be release of channels from direct inhibition by cell Ca2" (22). Incubating the tissue with aldosterone for longer periods (e.g., 6-16 hr) produced an additional increase in ISC that was sustained by vesicles.…”
Section: Figuresupporting
confidence: 81%
“…The possible explanations are focused upon the elevation in [Ca 2+ ] i in the medium or alternation in interaction of Ca 2+ and ENaCs due to changes in pH o . The ability of Ca 2+ to inhibit Na + uptake in toad bladder was greatly reduced by decreasing pH i from 7.4 to 7.0 (Garty et al, 1987). In this case, it would be expected that a decrease of pH i may relieve the inhibition of the channel by Ca 2+ .…”
Section: Low Intracellular Ph Reduced Enac Open Probabilitymentioning
confidence: 95%
“…Trans epithelial Na + transport rate is increased by intracellular alkalization but decreased by intracellular acidosis (Blokkebak-Poulsen et al, 1991;Harvey et al, 1988;. Controversially, in toad bladder, acidification of the cytoplasm can stimulate Na + transport (Garty et al, 1987;Leaf et al, 1964). Electrophysiology experiments based on transfected oocytes and A6 cells demonstrated that the α subunit of ENaC is directly regulated by pH i (Chalfant et al, 1999) and a reduction of pH i decreased ENaC activity.…”
Section: Namentioning
confidence: 99%
“…Taylor & Windhager (1979) suggested that luminal Na+ conductance can be regulated by an elevated cell Ca2+ concentration that might be involved in a feedback mechanism. Although the cellular mechanism whereby intracellular Ca2+ inhibits the conductance remains unclear, Ca2+ might directly block the Na+ channels by binding to a site on the cytoplasmic face of the channel protein (Chase & Al-Awquati, 1983;Garty, Asher & Yeger, 1987). There is also evidence that Ca2+ inhibits ap>al Na+ permeability indirectly by activating protein kinase C (Ling & Eaton,1°I t has been reported that in rabbit CCD, PGE2 increases celiJar Ca2+ by releasing Ca2+ from intracellular stores (Breyer, Jacobson & Hebert, 1990;Hebert et al, 1991).…”
Section: Role Of Ca2+mentioning
confidence: 99%